SOSILASISI PENERAPAN SISTEM PENDUKUNG KEPUTUSAN METODE SAW UNTUK PEMILIHAN MURID TERBAIK DI SANGGAR TARI SIDIMPUAN IDOL GRUB PADANGSIDIMPUAN - Hanifah Nur Nasution; Thofik Hidayat; Ermawita; Sari Wahyuni Rozi Nasution; Asrika Amanda Sari Hasibuan; Rahmat Wahid; Muhammad Fadly (LPPM UNIKS, 2026)
Dance studios are a platform for talent development and cultural preservation that plays a vital role in fostering human resources in the arts. However, the assessment and selection process for the best students at the Sidimpuan Idol Group Padangsidimpuan Dance Studio is still carried out manually and subjectively, resulting in a long time, risk of calculation errors, and a lack of objectivity. This community service activity aims to provide a solution in the form of implementing a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to assist managers and trainers in conducting assessments quickly, accurately, and transparently. The implementation method includes observation, socialization, system usage training, and mentoring. The system was developed using the PHP programming language, MySQL database, and the Bootstrap framework. The assessment criteria used include dance movement techniques, expression and appreciation, and discipline. The results of the activity show that the system developed is well-received, with a system feasibility validation rate reaching 96% and a user satisfaction rate of 100%. Through this activity, studio partners have a structured assessment tool, reducing subjectivity, and increasing the efficiency and quality of dance coaching.